Effects of Enzymatic Degradation after Loading in Temporomandibular Joint. (February 2015) - Asakawa-Tanne, Y.; Su, S.; Kunimatsu, R.; Hirose, N.; Mitsuyoshi, T.; Okamoto, Y.; Tanaka, E.; Tanne, K.; Tanimoto, K.
Synovial fluid of the joint decreases friction between the cartilage surfaces and reduces cartilage wear during articulation. Characteristic changes of synovial fluid have been shown in patients with osteoarthritis (OA) in the temporomandibular joint (TMJ). OA is generally considered to be induced by excessive mechanical stress. However, whether the changes in synovial fluid precede the mechanical overloading or vice versa remains unclear. In the present study, our purpose was to examine if the breakdown of joint lubrication affects the frictional properties of mandibular condylar cartilage and leads to subsequent degenerative changes in TMJ. We measured the frictional coefficient in porcine TMJ by a pendulum device after digestion with hyaluronidase (HAase) or trypsin. Gene expressions of interleukin-1β (IL-1β), cyclooxygenase-2 (COX-2), matrix metalloproteinases (MMPs), type II collagen, and histology were examined after prolonged cyclic loading by an active pendulum system. The results showed that the frictional coefficient increased significantly after HAase (35%) or trypsin (74%) treatment. Gene expression of IL-1β, COX-2, and MMPs-1, -3, and -9 increased significantly in enzyme-treated TMJs after cyclic loading. The increase in the trypsin-treated group was greater than that in the HAase-treated group. Type II collagen expression was reduced in both enzyme-treated groups. Histology revealed surface fibrillation and increased MMP-1 in the trypsin-treated group, as well as increased IL-1β in both enzyme-treated groups after cyclic loading. The findings demonstrated that the compromised lubrication in TMJ is associated with altered frictional properties and surface wear of condylar cartilage, accompanied by release of pro-inflammatory and matrix degradation mediators under mechanical loading.